Collagenous colitis. Issue 5 (May 1986) - Kingham, J G; Levison, D A; Morson, B C; Dawson, A M
Abstract : Clinical and pathological aspects of six patients with collagenous colitis are presented. These patients have been observed for between four and 15 years and the evolution of the condition is documented in three (cases 1, 3 and 5). Management and possible pathogenetic mechanisms of this enigmatic condition are discussed.